2019
DOI: 10.1177/0093854819867373
|View full text |Cite
|
Sign up to set email alerts
|

Bearing the Weight of Imprisonment: The Relationship Between Prison Climate and Well-Being

Abstract: Little is known about the relative influence of shared and individual perceptions of prison climate on adjustment to incarceration. This study investigated the relationship between prison climate and well-being among a sample of 4,538 adults incarcerated in the Netherlands. Prison climate dimensions were considered both as prison unit-level variables and as individual-level perceptions. Multilevel analysis results showed that most variance for well-being is found at the individual rather than the unit level. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 65 publications
3
26
0
1
Order By: Relevance
“…Similarly, whilst related to suicidal thoughts, aspects of the prison regime were not associated with the transition to suicide attempt. Previous studies have documented that prisoners' negative perceptions of the correctional climate (relating to autonomy, safety, meaningful activities, and relationships) are associated with poor mental health [40][41][42]. Although a recent meta-analysis [4] and several qualitative investigations [43,44] Consistent with studies highlighting that exposure to suicidal behaviour of others is associated with the transition from ideation to attempt in youth [11,35], we found that prisoners exposed to suicidal behaviour of incarcerated peers were twice as likely to act on their suicidal thoughts relative to those with no such exposure.…”
mentioning
confidence: 99%
“…Similarly, whilst related to suicidal thoughts, aspects of the prison regime were not associated with the transition to suicide attempt. Previous studies have documented that prisoners' negative perceptions of the correctional climate (relating to autonomy, safety, meaningful activities, and relationships) are associated with poor mental health [40][41][42]. Although a recent meta-analysis [4] and several qualitative investigations [43,44] Consistent with studies highlighting that exposure to suicidal behaviour of others is associated with the transition from ideation to attempt in youth [11,35], we found that prisoners exposed to suicidal behaviour of incarcerated peers were twice as likely to act on their suicidal thoughts relative to those with no such exposure.…”
mentioning
confidence: 99%
“…Previous studies have documented that prisoners' negative perceptions of the correctional climate (relating to autonomy, safety, meaningful activities, and relationships) are associated with poor mental health. [39][40][41] Although a recent meta-analysis 4 and several qualitative investigations 42,43 support the fact that institutional factors and prison experiences influence one's risk of suicide, no studies to date have examined their differential associations with distinct stages of the suicidal process. Pending replication, our data suggest that factors relating to the prison environment contribute to the development of suicidal thoughts, but do not impact the progression to suicide attempt.…”
Section: Discussionmentioning
confidence: 99%
“…The medical and psychosocial relevance of these issues is constantly increasing in line with the worldwide growth in the number of incarcerated people. Investigating the psychological effects of the imprisonment is fundamental in order to reduce inmates' pain and suffering and to prevent long-lasting consequences beyond the prison sentence itself (van Ginneken et al, 2019;Ward & Stewart, 2003). Living in prison is a traumatic and illness-risk experience: Some of the main factors related to inmates' health during their imprisonment are traceable to overcrowding (Haney, 2012), family deprivation (Hagan & Dinovitzer, 1999), fear of the unknown, the emotional climate of distrust (Picken, 2012), and the isolation.…”
Section: The Psychological Effects Of Imprisonmentmentioning
confidence: 99%